1995
DOI: 10.1021/jm00016a009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of a Series of Substituted Benzo[a]phenanthridines as Agonists at D1 and D2 Dopamine Receptors

Abstract: Dihydrexidine [4;(+/-)-trans-10,11-dihydroxy-5,6,6a,7,8, 12b-hexahydrobenzo[a]phenanthridine (DHX)], the first high-affinity full D1 agonist, also is known to have significant D2 activity. The present work reports the synthesis and pharmacological activity of a series of analogs substituted in the pendent phenyl ring (i.e., 2-, 3-, or 4-position). (+/-)-trans-2-Methyl-10,11-dihydroxy-5,6,6a,7,8, 12b-hexahydrobenzo[a]phenanthridine (5) was a high-affinity D1 agonist, having approximately 4-fold greater D1 vs D2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…To this end, the role of D5 receptors in the stimulatory effects of DHX on hippocampal ACh efflux has not been studied as it has been studied for the D1 receptor partial agonist SKF 38393 (see Laplante et al 2004), where it was shown that its stimulatory effects on ACh release in the hippocampus were prevented in D5 receptor knockout mice. DHX has been shown to bind to DA D2 receptors, where it functions as an agonist in vitro (Brewster et al 1990;Knoerzer et al 1995) and, at high doses, in vivo (see, e.g., Darney et al 1991). This is the reason why we first showed that the stimulatory effects of the 18-mg/kg dose of DHX (which we used in the chronic studies) on hippocampal ACh release were completely abolished by SCH 23390 (see above).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, the role of D5 receptors in the stimulatory effects of DHX on hippocampal ACh efflux has not been studied as it has been studied for the D1 receptor partial agonist SKF 38393 (see Laplante et al 2004), where it was shown that its stimulatory effects on ACh release in the hippocampus were prevented in D5 receptor knockout mice. DHX has been shown to bind to DA D2 receptors, where it functions as an agonist in vitro (Brewster et al 1990;Knoerzer et al 1995) and, at high doses, in vivo (see, e.g., Darney et al 1991). This is the reason why we first showed that the stimulatory effects of the 18-mg/kg dose of DHX (which we used in the chronic studies) on hippocampal ACh release were completely abolished by SCH 23390 (see above).…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant D 1 activation is also unlikely to play a role. For example, although DHX is a D 1 full agonist, PrDHX is a low intrinsic activity partial D 1 agonist (Knoerzer et al, 1995). Therefore, one would expect very different functional patterns if D 1 receptors were critical to the current phenomena (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Extension of the hydrophobic bulk to an ethyl group (compound 5b ) incurred an even greater loss of D 1 affinity (D 1 K i = 185 nM) compared to 2 . Although the ethyl substituted analog of DHX (compound 4 ) also displayed affinity lower than the unsubstituted compound [19], its chroman isostere 5b clearly shows a more dramatic negative effect of the ethyl substituent on affinity.…”
Section: Discussionmentioning
confidence: 99%
“…In the DHX series, substitution on the β-phenyl ring at the 2-position with methyl and ethyl groups gave ligands with increased D 1 selectivity as a result of decreased D 2 affinity [19] (Figure 2). We hypothesized that compounds with analogous substitution at the 11-position of 2 would display D 1 -selectivity greater than the parent compound.…”
Section: Introductionmentioning
confidence: 99%